Plasma branched-chain amino acid concentrations in individuals without cardiovascular diseases versus patients diagnosed with hypertension and coronary artery disease - M. V. Kozhevnikova; E. O. Korobkova; A. V. Krivova; A. V. Kukharenko; N. E. Moskaleva; K. M. Shestakova; N. V. Mesonzhnik; A. A. Ageev; A. A. Boldin; A. Brito; S. А. Appolonova; E. V. Privalova; et al. (Рациональная фармакотерапия в кардиологии)
Aim. Branched-chain amino acids (BCAAs) have been postulated as potential indicators of cardiovascular risk. The objective of this study was to explore the relationship between plasma BCAAs and different stages of cardiovascular disorders.Material and methods. In our cross-sectional study, plasma BCAAs (valine, leucine and isoleucine) in individuals without cardiovascular diseases (CVDs) (nonCVD group, total n=27, with n=16 healthy, but with metabolic disorders) were compared to patients diagnosed with CVDs [CVD group, total n=109, being n=61 hypertension (n=31 with signs of beginning of myocardial remodeling) and n=48 patients with coronary artery disease (CAD)].Results. The plasma concentration of BCAAs was significantly higher in the group of patients with cardiovascular disease compared with the healthy group (p<0.05 for all amino acids tested): valine concentration was 238.7 [219.6; 267.0] μM in the non-CVD group and 261.2 [233.8; 298.7] μM in the CVD group; leucine concentration was 134.8 [122.4; 153.2] μM and 146.8 [129.0; 166.6] μM, respectively; and isoleucine 72.7 [65.3; 84.4] μM and 81.7 [68.0; 96.2] μM, respectively. Leucine and isoleucine concentration levels were minimal in the healthy participant subgroup and maximal in the IBS patient subgroup. No statistically significant differences in BCAAs concentrations were found in the subgroups without CAD. Significant increases in concentrations were observed in the subgroups of patients with CAD as follows: valine concentration was 256.3 [219.0; 297.9] μM in hypertension group and 261.7 [236.5; 307.5] μM in CAD group; leucine concentration was 141.8 [123.5; 166.6] μM and 154.1 [134.7; 172.7] μM, respectively, and isoleucine 72.8 [65.7; 94.0] μM and 85.7 [74.9; 101.7] μM, respectively. BCAAs profiles in all participants with metabolic disorders had “good” diagnostic accuracy with area under the receiver operating characteristics curve being 0.72, 0.70 and 0.70 for valine, leucine and isoleucine, respectively.Conclusion. BCAAs concentrations are elevated with higher severity of the cardiovascular disorder and exhibit potential as early independent indicators of coronary artery disease.